MARS/NDRI/KSU Communications Workshop: Part 5. Summary of Responses to Day 1 Nominal Group Questions - Leslie, John F.; Harvey, Jagger J.W.; Morris, Jeffery B. (My University, 2022)
A. Identify Key Issues Regarding Mycotoxins of Relevance to Consumers – Pages 1-3 B. Identify Key Issues Regarding Mycotoxins of Relevance to Producers, Traders & Distributors – Pages 4-5 C. Identify Key Issues Regarding Mycotoxins of Relevance to Health Professionals – Pages 6-8 D. Identify Key Issues Regarding Mycotoxins of Relevance to Educators, Trainers & Researchers – Pages 9-11 E. Identify Key Issues Regarding Mycotoxins of Relevance to Policy Makers & Regulators – Pages 12-14
Keywords: Aflatoxin; Food Safety; Mycotoxins; Nepal; Public Health; Risk Communication